Design and manufacture of coconut shell charcoal crusher for briquette - Andi Gilang Wira Pratama; Zaini; Azwinur (Journal of Mechafa Engineering and Fabrication, 2024)
Coconut shell waste in the community is often not utilized, so a solution is needed, one of which is by processing it into briquettes. Charcoal briquettes are solid fuels that contain carbon, have high calorific value, and can burn for a long time. These briquettes are made from organic waste, such as dry leaves, coconut shells, rice husks, and sawdust. The purpose of this study was to design a coconut shell charcoal crusher as a raw material for briquettes, with the hope of reducing coconut shell waste, increasing its economic value, and providing an alternative fuel for household needs. The process of making the tool begins with frame design, iron cutting, welding using the SMAW method, assembly, and finishing. The results of the study showed that the results of making a coconut shell charcoal crusher for briquette raw materials can function well. The distribution of the resulting size shows that the machine has a consistent ability to produce fine particle sizes, which are in accordance with the needs of briquette raw materials. The efficiency of time per kilogram of material processed tends to vary depending on the capacity used